Jesus and the forces of death: the gospels' portrayal of ritual impurity within first-century Judaism - Thiessen, Matthew (Baker Academic, 2020)
"Correcting a popular misconception, this book demonstrates that the Gospel writers present Jesus within Judaism, opposing ritual impurity but not the Jewish law itself"--